Pioneer Rocketry - 2016 Midwest Rocket Competition - Ellenberger, Jake (Proceedings of the Wisconsin Space Conference, 2017)
The objective of the 2016 Midwest Rocket Competition was to use an active drag system to control the altitude of the rocket. The rocket was to fly twice, once with the system deactivated then again with the system active. The goal was for the active drag system to get the highest altitude of the second flight to be 75% of the un-deployed flight. The electric system onboard needed to both control the drag system as well as record the data needed to estimate the drag coefficient throughout the flight. At competition the rocket was flown a total of three times and performed as expected. The rocket was able to achieve a reduction of 78% thus placing Pioneer Rocketry third in the competition. The following report details the design and construction of Pioneer Rocketry’s rocket Skybreaker, along with information regarding Pioneer Rocketry’s growth as both an educational and professional organization.